Soil correction for planting bermudagrass using steel slag or limestone - Oliveira, Mauricio Roberto de [UNESP]; Fernandes, Dirceu Maximino [UNESP]; Bôas, Roberto Lyra Villas [UNESP]; Backes, Clarice; Godoy, Leandro José Grava de [UNESP]; Santos, Alessandro José Marques do (FapUNIFESP (SciELO), 2020)
Limestone is the most commonly used acidity-correction agent in tropical soils. However, steel slag can be an alternative for turfgrass production areas because it contains silicon, which can increase turfgrass tolerance to biotic and/or abiotic stresses. This study was developed to evaluate the effect of the application of steel slag, as compared with limestone, on a bermudagrass sod production system. The experiment was carried out in Botucatu-SP, Brazil, in a randomized block design arranged in a factorial scheme 2 × 5 with 4 replications. Treatments consisted of two correctives (steel slag and limestone) and their rates, which were calculated to raise the soil base saturation to 12% (current), 30%, 50%, 70% and 90%. The application of lime and steel slag rates had positive effects on soil chemical attributes related to acidity correction, such as pH, Ca, Mg, H + Al, Al, CEC, SB, and base saturation (%). The slag provided higher levels of P, Ca, and Si, whereas limestone increased the Mg soil content. Steel slag provided a higher ground cover rate for bermudagrass than limestone at 114 and 161 days after transplanting (DAT), with maximum cover rate achieved with 60% base saturation at 161 DAT. The turfgrasses treated with slag showed a higher amount of roots, rhizomes, and stolons when compared with those treated with limestone. It is suggested the use of steel slag and, in calculating the need for corrective, 90% soil base saturation.
Keywords: Cynodon sp.; lawn; liming; silicon